Prenatal diagnosis and molecular cytogenetic characterization of a de novo duplication of 2q12.2→q13 encompassing MALL, NPHP1, RGPD6 and BUB1 - Chih-Ping Chen; Shin-Wen Chen; Schu-Rern Chern; Peih-Shan Wu; Fang-Tzu Wu; Yen-Ting Pan; Chen-Wen Pan; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a de novo duplication of 2q12.2→q13 encompassing MALL, NPHP1, RGPD6 and BUB1. Case report: A 36-year-old, primigravid woman underwent amniocentesis at 16 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XX,dup(2) (q12.2q13). Simultaneous array comparative genomic hybridization (aCGH) analysis revealed a 6.1-Mb 2q12.2q13 duplication. aCGH analysis of the parental bloods did not find such a duplication. Prenatal ultrasound was unremarkable. After genetic counseling, the parents decided to terminate the pregnancy at 21 weeks of gestation, and a 420-g female fetus was delivered with no gross abnormalities. Postnatal cytogenetic analysis of the umbilical cord confirmed the prenatal diagnosis. The parental karyotypes were normal. aCGH analysis of the umbilical cord revealed the result of arr [GRCh37 (hg19)] 2q12.2q13 (107, 132, 950-113,065,779) × 3.0 with a 2q12.2→q13 duplication encompassing 20 OMIM genes including MALL, NPHP1, RGPD6 and BUB1. Polymorphic DNA marker analysis of quantitative fluorescence polymerase chain reaction (QF-PCR) on the DNAs extracted from the umbilical cord and parental bloods confirmed a maternal origin of the duplication of 2q12.2→q13. Conclusion: Amniocentesis may incidentally detect a de novo chromosomal segmental duplication of maternal origin in the fetus. The genetic information acquired by molecular analyses such as aCGH and QF-PCR are useful for genetic counseling under such a circumstance.